Adult-Onset linear verrucous epidermal nevus in an Indian male - U K Sudhir Nayak; Shrutakirthi D Shenoi; Rupika Singh; Kanthilatha Pai (Clinical Dermatology Review, 2022)
Verrucous epidermal nevus is the most common form of epidermal nevi with usual onset at birth or early life. Adult onset is rare, and we report a case of verrucous epidermal nevi with onset in the fourth decade, dermatoscopy and histopathology of which were consistent with verrucous epidermal nevi.